Legal Evaluation of the Doctrine of General Average Loss: The Purpose in Modern Day Maritime Transaction - Edidiong Jacob Udo; Okubor Cecil Nwachukwu; Patrick Chukwunonso Aloamaka (Universitas Negeri Makassar, 2021)
The paper unravels the purpose of the doctrine of general average loss in modern day maritime transactions through a critical examination of relevant literature on the subject area. In the bid to achieve this objective, resort is made to adopting a theoretical and doctrinal methodology wherein relevant primary and secondary source materials were utilized. This includes a critical examination of relevant statutory provisions, case law and scholarly literature. The information obtained through these sources was subjected to a contextual and descriptive analysis. The paper finally reaches its findings by revealing that this age long concept has not lost its usefulness and is still relevant in modern day’s maritime transaction. It therefore recommends the protection of lives at sea and of maritime property is of paramount importance and must be encouraged by courts without such encouragements the maritime industry could be one so fraught with dangers and risk that few, if any, would reasonable engage in such day-to-day commercial transactions.